2014
DOI: 10.1099/jmm.0.075044-0
|View full text |Cite
|
Sign up to set email alerts
|

Zinc enhances the phototoxic effect of blue light against malodour-producing bacteria in an experimental oral biofilm

Abstract: Oral malodour is thought to be caused mainly by the production of volatile sulfide compounds (VSCs) by anaerobic Gram-negative oral bacteria. Previous studies have shown that these bacteria are susceptible to blue light (400-500 nm wavelength). In the present study, we tested the effect of blue light in the presence of zinc, erythrosine B or both on malodour production in an experimental oral biofilm. Biofilms were exposed to a plasma-arc light source for 30, 60 and 120 s (equal to energy fluxes of 41, 82 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Previous studies demonstrated the phototoxic effect of high intensity blue light against malodour producing bacteria in a salivary incubation assay [13]. This effect was enhanced in the presence of zinc serving as a possible photocatalytic agent [16]. In the present study, we tested the effect of various red dyes photosensitizers on this process in an experimental biofilm system.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies demonstrated the phototoxic effect of high intensity blue light against malodour producing bacteria in a salivary incubation assay [13]. This effect was enhanced in the presence of zinc serving as a possible photocatalytic agent [16]. In the present study, we tested the effect of various red dyes photosensitizers on this process in an experimental biofilm system.…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies we showed that VSC producing bacteria were suseptible to high intensity blue light [13] and that this phototoxic effect was enhanced by the addition of zinc ions [16]. The aim of the present study was to test the hypothesis that red dye photosensitizers may promote the phototoxic effect of high intensity blue light against malodor producing bacteria in an experimental oral biofilm model.…”
Section: Introductionmentioning
confidence: 86%
“…They also possess mild antibacterial effects. Sterer et al reported that zinc acetate enhanced the effectiveness of aBL against malodour-producing bacteria in an experimental oral biofilm (Sterer et al, 2014). Biofilms were exposed to aBL (400–500 nm) at the exposures of 41, 82, and 164 J/cm 2 , respectively with or without the addition of zinc acetate.…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…First, zinc acetate (ZnAc) has been shown to inhibit ciprofloxacin- as well as zidovudine-induced recA gene expression at 200 µM in a Shiga toxin-producing E. coli strain [ 33 ]. Sterer et al found that adding 1 % ( w / v ) of ZnAc when irradiating a biofilm with a light source emitting a wavelength of 400–500 nm and a dose of 41, 82 and 164 J/cm 2 increased the inactivation of malodor-producing bacteria compared to aBL treatment alone [ 60 ]. In the present work, 475 nm aBL therapy was performed with a concentration of 500 µM ZnAc with E. coli K12 and E. coli TOP10.…”
Section: Discussionmentioning
confidence: 99%